Does Participatory Budgeting Alter Public Spending? Evidence From New York City. Issue 9 (October 2020) - Calabrese, Thad; Williams, Dan; Gupta, Anubhav
Participatory budgeting is described as a direct-democracy approach to resource allocation decision making. Theories assume it changes how public resources are spent by moving decisions from elected officials to citizens. The literature does not consider how earmarking—in which legislators direct parts of public budgets directly—might affect the impact of such policy devices. New York City's participatory budgeting process which uses earmarks is analyzed to determine spending changes. Officials involved fund more projects at lower average amounts than those not involved but do not change the areas of funding, all of which is expected in systems of budgetary earmarks controlled by legislators.